Toxicity and removal efficiency of pharmaceutical metabolite clofibric acid by Typha spp. – Potential use for phytoremediation? - Dordio, A. V. (2012)
A study was conducted to assess Typha spp.’s ability to withstand and remove, from water, a metabolite of blood lipid regulator drugs, clofibric acid (CA). At a concentration of 20 lg L 1, Typha had removed >50% of CA within the first 48 h, reaching a maximum of 80% by the end of the assay. Experimental conditions assured that photodegradation, adsorption to vessel walls and microbial degradation did not contribute to the removal. Exposure to higher CA concentrations did not affect Typha’s photosynthetic pigments but the overall increase in enzyme activity (ascorbate and guaiacol peroxidases, catalase, superoxide dismutase) indicates that both roots and leaves were affected by the xenobiotic. Eventually, Typha seemed able to cope with the CA’s induced oxidative damage suggesting its ability for phytoremediationof CA contaminated waters.